A tale of two clusters: high technology industries in Cambridge. (7th September 2004) - Cooke, Philip; Huggins, Robert
This paper offers a textured case analysis of biotechnology and ICT clusters in Cambridge (UK). Arguing that this is the superior method by which an understanding of clustering processes may be gained, until econometric methods move beyond their infancy in analysing socio-economic interaction, it is shown that clustering in this university city is pronounced, changing and, in some instances, problematic. The two clusters are embedded in network relationships among a multitude of actors of consequence. These networks are partially exclusive, especially regarding new activities like leisure software/computer games that may be less "scientific" than core cluster activities. There are diseconomies of agglomeration and labour market mismatches requiring educational provision of a less scientific and more technical nature. The demand for land is insatiable but heavily constrained by zoning regulations. Nevertheless, the clusters show no sign of degrading under these circumstances, rather the opposite of continuing dynamism.